Description of Nursing Implementation with Main Nursing Problem on Child Diarrhea of The Regional Hospital in Besuki Residency - Alfy Meilinda Hapsari; Lantin Sulistyorini (Pustaka Kesehatan, 2022)
Diarrhea are one of the diseases that causes the death of children number two in 2016 and has the main causative factors, namely groups of viruses, bacteria and parasites. The purpose of this study was to find out a description of nursing implementation in diarrhea children aged 0-18 years in the area of Besuki residency which is famous for its agro-cultural with high mortality problems in children. This research method was descriptive with a retrospective approach and use a purposive sampling technique. The sample in the study was 199 diarrhea children aged 0-18 years of the regional hospital in the area of Besuki residency. Data collection tools in this study is using checklist sheets. The result of the study showed diarrhea nursing problems that often arise with observational nursing action, namely pulse strength monitoring, number of frequencies, monitoring a number of respiratory. Observation has influence which is high enough to detect changes in life support systems. Vital signs are a statistical measure, especially for clients who are medically unstable, can know the baseline data to determine the stress response of physiology or psychology, concerning factors related to the existing disease and to assess the client's response to the conversion given by health workers. Observation is a basic method of assessment and assessment for clients to find out clinical signs in establishing a diagnosis of disease and for planning appropriate medical therapy.